Pengaruh Non Performing Loan, Loan to Deposit Ratio, Return on Assets dan Bopo terhadap Capital Adequacy Ratio pada PT Bank Pembangunan Daerah Kalimantan Selatan - Arfie Yasrie; Diana Diana (Sekolah Tinggi Ilmu Manajemen Indonesia (STIMI) Banjarmasin, 2026)
This study aims to analyze the effect of Non-Performing Loans (NPL), Loan to Deposit Ratio (LDR), Return on Assets (ROA), Operating Costs to Operating Income (BOPO) on the Capital Adequacy Ratio (CAR) at PT. Bank Pembangunan Daerah Kalimantan Selatan. The study was conducted using secondary data in the form of financial reports of PT. Bank Pembangunan Daerah Kalimantan Selatan during 2017-2023. Hypothesis testing was conducted using t-test and F-test using SPSS 25 software. The research results provided findings, (1) Non-Performing Loans (NPL) do not affect the Capital Adequacy Ratio (CAR) at PT. Bank Pembangunan Daerah Kalimantan Selatan. (2) Loan to Deposit Ratio (LDR), partially affects the Capital Adequacy Ratio (CAR) at PT. Bank Pembangunan Daerah Kalimantan Selatan. (3) Return On Assets (ROA) does not affect the Capital Adequacy Ratio (CAR) of PT. Bank Pembangunan Daerah Kalimantan Selatan (4) Operating Costs to Operating Income (BOPO) does not affect the Capital Adequacy Ratio (CAR) at PT. Bank Pembangunan Daerah Kalimantan Selatan. (5) Non-Performing Loans, Loan to Deposit Ratio, Return On Assets, and Operating Costs to Operating Income (BOPO) simultaneously affect the Capital Adequacy Ratio (CAR) at PT. Bank Pembangunan Daerah Kalimantan Selatan.